Experimental drugs for fallopian cancer: promising agents in the clinical trials and key stumbling blocks for researchers. (2nd December 2022) - Cioffi, Raffaella; Galli, Federica; Rabaiotti, Emanuela; Candiani, Massimo; Pella, Francesca; Candotti, Giorgio; Bocciolone, Luca; De Marzi, Patrizia; Mangili, Giorgia; Bergamini, Alice
ABSTRACT: Introduction: Fallopian tube carcinoma (FC) as a single entity is a rare disease. Although its diagnosis is increasing thanks to the widespread use of prophylactic salpingectomy, there are no clinical trials exclusively designed for FC. Areas Covered: This review aims at identifying the most promising trials and future therapeutic pathways in the setting of FC. Expert Opinion: Hot topics in FC treatment include the consequences of using PARP inhibitors (PARPi) as first-line therapy, ways to overcome platinum resistance, and the role of immunotherapy. Patient selection is a key point for future development of target therapies. Next-generation sequencing (NGS) is one of the most investigated technologies both for drug discovery and identification of reverse mutations, involved in resistance to PARPi and platinum. New, promising molecular targets are emerging. Notwithstanding the disappointing outcomes when used by itself, immunotherapy in FC treatment could still have a role in combination with other agents, exploiting synergistic effects at the molecular level. The development of cancer vaccines is currently hampered by the high variability of tumor neoantigens in FC. Genomic profiling could be a solution, allowing the synthesis of individualized vaccines.